Bits & pieces - Maberry, Jonathan (Maberry, Jonathan. Rot & Ruin, 2015)
Twenty-two short stories, eleven of which were previously published, based on the Rot & Ruin series in which fifteen-year-old Benny Imura and his friends fight a zombie plague in a post-apocalyptic America. Includes a related comic book script.